Effects of Maternal Exposure to Lamotrigine during Pregnancy on Gonadal Toxicity in Fetus Rats: - Aryan, Hoda; Movassaghi, Shabnam; Ghasemi, Amir; Darabi, Roksana (Galen Medical Journal, 2020)
Background: Lamotrigine is one of the newest antiepileptic drugs that is used as one of the most common treatments in pregnancy. Since the investigation of the teratogenic effects of lamotrigine is very limited and there is no report of its teratogenic effects on fetal gonads, we aimed to investigate the teratogenic effects of lamotrigine on embryonic gonads. Materials and Methods: This study was performed on nine female Wistar female rats (8 weeks, weighing 180-200 mg). At first, the animals were inspected regularly by the preparation of vaginal smear and in the estrus phase in separate cages of mating, and after observing the vaginal plaque, were randomly divided into three groups (n=3). Control group did not receive any treatment. In the lamotrigine group (20mg/kg), and the vehicle group (same volume of normal saline) were injected intraperitoneally from days 8 to 13 of pregnancy. On day 20, animals were anesthetized by sodium pentobarbital (40 mg/kg), and embryos were extracted through laparotomy. First, fetuses were weighed, and their height (crown-rump length) was measured. Then the gonads of the fetuses were removed and, stained with H & E, and examined by optical microscope. Results: Our results showed that in the lamotrigine group, the number of seminiferous tubules and Sertoli cells in the male embryos and the number of oocytes in the female embryos decreased significantly compared to the control and vehicle groups (Pâ‰¤0.05). Conclusion: The results of this study showed that treatment with 20 mg/kg lamotrigine in mothers during pregnancy could cause damage to fetal gonads. [GMJ.2020;9:e1557]